Effect of dentin pre-treatment on smear layer thickness: an ultrastructural study - Mahdan, Mohd Haidil Akmal; Samani, Nur Sarahniza; Mohd Ridzuan, Syakirah; Maideen, Mohd. Maizam (Microscopy Society Malaysia, 2020)
The aim of thisstudy was to investigate the morphological changes of etched dentin by sodium hypochlorite (NaOCl) pre-treatment method applied for different durationsand smear layer (SL)thickness. Sixtyhuman molars were used in this study and sectioned at thecoronal part to expose a flat dentin disc. They were ground with #180-or #600-grit silicon carbide papers, to produce thick and thin SL respectively. All specimens wereassignedinto 6 groups; G1: control; G2: Acid Etch (AE); G3, G4, G5 and G6: AE + 10% NaOCl for 15, 30, 60, and 120s, respectively. Specimens were observed under aScanning Electron Microscope and the photomicrographs were classified according to the following scores: 0: presence of SL; 1: No smear layer+ non-altered collagen fibrils; 2: No smear layer+ slightly altered collagen fibrils; 3: No smear layer+ severely altered collagen fibrils; and 4: No smear layerand absence of collagen fibrils. KruskalWallis showedall groups treated with NaOCl solution were significantly different, and alteration regarding the collagenfibrils network.The higher the duration of NaOCl pre-treatment, the more alteration of collagen fibrils occured